2016
DOI: 10.1039/c5ra24819a
|View full text |Cite
|
Sign up to set email alerts
|

Variations of lignin–lignin and lignin–carbohydrate linkages from young Neosinocalamus affinis bamboo culms

Abstract: Three lignin–carbohydrate complex (LCC) preparations were isolated to elucidate the variations of chemical linkages during growth in the early development stages of Neosinocalamus affinis bamboo culms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…LCC linkage plays a crucial role in wood structure, since all lignin moieties in softwoods [ 19 ] and 47–66% of lignin fragments in hardwoods [ 20 ] are bound to carbohydrates, mainly to hemicellulose [ 21 ]. Numerous studies report the presence of LCC in native biomass materials in coniferous, deciduous, and non-wood plants [ 19 , 22 – 25 ]. Due to its strong bonding, the presence of LCC affects the overall extraction of lignin and carbohydrates [ 16 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…LCC linkage plays a crucial role in wood structure, since all lignin moieties in softwoods [ 19 ] and 47–66% of lignin fragments in hardwoods [ 20 ] are bound to carbohydrates, mainly to hemicellulose [ 21 ]. Numerous studies report the presence of LCC in native biomass materials in coniferous, deciduous, and non-wood plants [ 19 , 22 – 25 ]. Due to its strong bonding, the presence of LCC affects the overall extraction of lignin and carbohydrates [ 16 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…2). Both of H H and H L showed obvious absorption at 3408 cm À1 and 2939 cm À1 , which were attributed to the O-H stretching vibration of the hydroxyl groups and C-H (CH 2 and CH 3 ) stretching vibrations in hemicelluloses, 15 respectively. The FT-IR spectra also demonstrated that the hemicelluloses can be obtained from holocellulose without cleaving the acetyl ester groups by the treatment with water, in which the absorption around 1736 cm À1 represented the C]O stretching of acetyl groups in the region of the carbonyl stretching vibration.…”
Section: Composition Study Of H L and H Hmentioning
confidence: 99%
“…Fourier transform infrared (FT-IR), as a rapid and nondestructive method, has been vastly utilized for analyzing a variety of rich and unique materials including biological materials. 13,[15][16][17][19][20][21][22][23][24][25][26][27][28][29] IR spectra provide a beneficial information about the hydrogen bonding (intra-and inter-chain) and C-O bonding in cellulose. Several researchers studied the hydrogen bonding in cellulose I β and has demonstrated that FT-IR method is able to provide intense information about intrachain H-bond (O2-H2···O6 and O3-H3···O5) and interchain H-bond (O6-H6···O3`and O2`), located between 3500 and 3200 cm -1 .…”
Section: Analytical Sciencesmentioning
confidence: 99%
“…13,[21][22][23][24][25][26] Furthermore, FT-IR spectroscopy has been used as an indirect method to examine the lignin and carbohydrate linkage. [27][28][29]…”
Section: Analytical Sciencesmentioning
confidence: 99%